Production and Product Development Natural Spraydried Pandan (Pandanus Amaryllifolius) Powder - Loh, Seng Kean (2005)
A study was performed to optimize the production process of encapsulated pandan powder using response surface methodology (RSM). The study was inclusive of an evaluation of two types cf carbohydrates, namely maltodextrin and gum arabic, in the production of encapsulated pandan powder as an encapsulator. A product development of home made pandan ice cream was carried out to evaluate the effectiveness of encapsulated pandan powder as an ingredient in food. An optimum condition for production of encapsulated spray dried pandan powder was established. Inlet temperature of 170°C and speed rate of 6 rpm with constant outlet temperature of 90°C were shown to be the optimum conditions to produce encapsulated pandan powder. A combination of maltodextrin and gum arabic in the formulation of spray dried encapsulated pandan powder in terms of physicochemical properties and sensory scores was also carried out.A pandan flavored ice cream using encapsulated pandan powder as a colouring and flavouring agent was successfully developed. The optimum condition for formulation of pandan ice cream using spray dried encapsulated pandan powder was established. Pandan p~wderc onsentration of 3.41% and sugar concentration of 3.45% were shown to be the most acceptable conditions to proGuce pandan flavored ice cream.